Self-Ideal for Christian Adolescents in Overcoming Risky Premarital Sexual Behavior - Manurung, Hasanuddin (MID Publisher International, 2024)
Engaging in risky premarital sexual activity is a manifestation of expressing emotions or love through actions. These actions range from simple displays of affection, such as kissing, to having sexual relations outside the bonds of marriage. This behavior is driven by man's natural tendency for sexual gratification, both with opposite-sex and same-sex individuals. While premarital sexual activity that does not contain risk basically creates life in the form of connection, friendship, beauty, kindness, encouragement or motivation, as well as knowing how to express sexual desire so that we become who we really are and not participate in extramarital sex because it will open the soul, spirit (heart) and body to influences and dangers in the long and short term. In this study, the method used is a research method by applying a qualitative approach with literature study techniques. Data analysis is presented descriptively. Qualitative research is based on efforts to build a view of the object under study in detail, formed with words, and a holistic picture. This research begins with collecting data from various literature sources relevant to research, classifying data and formulating methods in data regularity. Data analysis is carried out by inductive analysis, which is analyzing data and then developed in accordance with the formulation of the problem. To overcome the problem of risky premarital sexual behavior, ideal-self quality is needed based on psychological aspects, Christian aspects and social aspects. In the psychological aspect, adolescents are required to have a superego so that they can distinguish right and wrong behavior so that their behavior can be accepted by society. In the aspect of Christianity, the superego is projected onto the external figure of Jesus Christ as a guide for youth in good and true behavior. In the social aspect, adolescents are required to act from the true self and be able to choose a community that can really shape the personality of adolescents.